TYPES OF FASCIATION IN PLANTS AND FACTORS AFFECTING ITS MANIFESTATION - S. N. Mayorov; A. V. Molchanova; L. L. Bondareva; V. I. Startsev (Овощи России, 2012)
The review deals with the phenomenon of fasciation and its types, as well as factors that contribute to its occurrence.